A produção da história local em Itumbiara/GO: outras histórias - Ferreira, Paula Marcele Oliveira (2024)
The dissertation was developed in the Postgraduate Program in History teaching at the Federal University of Uberlândia (ProfHistória/UFU). The theme is Local History. The general objective was to investigate the limitations and potential of teaching local history through the analysis of the teaching material available to teachers and local historiographical and memorialistic productions. The following objectives were specifically defined: i: Reflect on the teaching of History and the place of regional and local history; ii: Present the research scenario and analyze what has been produced about the History of Itumbiara, GO, Brazil; iii: Develop a Study Guide on the local history of Itumbiara, integrating a variety of sources and languages that reflect a decolonial perspective. The methodology adopted was based on a qualitative approach, inspired by decolonial studies, which highlight historically subordinated groups and subjects as protagonists. The guide documents significant historical events and challenges prevailing narratives, including other historically marginalized voices and experiences. The proposal is to promote education that dialogues with the cultural and social complexities of the local community, which can contribute to the training of teachers by inserting a critical and reflective approach into the curricula. The research highlights the importance of an approach to local history that avoids reproducing the dominant view and that considers different sources and protagonisms, contributing to a dialogical civic and historical formation.